Thermochromic phase change energy storage microcapsule as well as preparation method and application thereof
By using cellulose nanocrystals and resin prepolymers to form a strongly entangled interface structure, the stability and temperature response problems of existing microcapsules materials are solved, and efficient temperature discoloration and energy storage performance are achieved. , and the material is environmentally friendly and biodegradable.
Patent Information
- Application Number
- CN202411014334.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2024-12-13
AI Technical Summary
The existing microencapsulated temperature-discolored materials have defects such as poor mechanical properties, fast aging and decomposition, poor stability, low temperature response sensitivity, narrow temperature range of discoloration and energy storage, and are not environmentally friendly. Commonly used nanomaterials are sensitive to environmental conditions. Unstable structure and poor emulsification performance.
Cellulose nanocrystals are used as stable particles of Pickering emulsion, and combined with resin prepolymers to form a strong entangled disordered interface structure, which improves the mechanical properties and stability of microcapsules, and forms an outer covering layer through in-situ polymerization reaction to enhance The mechanical properties and environmental friendliness of the material.
It has achieved good stability, good coating effect, environmental protection and pollution-free, sensitive temperature response, reversible color change, wide temperature range of color change and energy storage, high thermal stability of the material, excellent energy storage performance .
Smart Images

Figure BDA0004965268050000091 
Figure HDA0004965268060000011 
Figure HDA0004965268060000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermochromic materials, and in particular to a thermochromic phase-change energy storage microcapsule and a preparation method and application thereof. Background Art
[0002] In order to improve the utilization rate of energy, phase change energy storage materials with high quality energy storage density and renewability have attracted great attention. Phase change energy storage materials are functional materials that can store or release a large amount of latent heat by changing their physical state at a certain temperature. However, when the phase change occurs, the liquid is easy to flow and leak. At present, an effective method is to use microcapsule technology for encapsulation.
[0003] Thermochromic materials have the property that their color changes with temperature. Compared with single compounds with thermochromic properties, organic thermochromic materials have easy-to-obtain raw materials and low prices. There are many types of organic substances that can be used as hidden agents, color developers and phase change materials, and they have received widespread attention. Organic thermochromic materials have the property of reversible color change from colored to colorless, but they are easily affected by the external environment. Therefore, researchers use the protective effect of microcapsules to encapsulate organic thermochromic materials and apply them to substrates, which not only expands the application range of thermochromic materials, but also enhances the convenience of using thermochromic materials.
[0004] Existing microencapsulated thermochromic materials have the defects of poor mechanical properties, fast aging and decomposition, poor stability, low temperature response sensitivity, narrow temperature range of discoloration and energy storage, and environmental protection. On the basis of conventional microcapsule materials, optimizing the preparation process and structure of microcapsules and improving their performance are still research hotspots in related fields. Compared with conventional emulsions, Pickering emulsions are ideal templates for synthesizing microcapsules. At present, there have been studies on the use of natural and sustainable nanomaterials such as proteins and polysaccharide particles for the preparation of Pickering emulsions, but these nanomaterials are more sensitive to changes in environmental conditions, unstable protein structure, easy aggregation, weak surface activity of polysaccharide particles, and poor emulsification performance. Therefore, it is necessary to seek more efficient natural and sustainable Pickering emulsion stabilized particles to promote the improvement of the performance of thermochromic phase change microcapsule energy storage materials, so as to obtain a thermochromic phase change energy storage microcapsule with environmental protection, good stability, sensitive temperature response, wide temperature range of discoloration and energy storage, good energy storage performance, and excellent overall performance. Summary of the invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a thermochromic phase-change energy storage microcapsule; the second purpose of the present invention is to provide a method for preparing such a thermochromic phase-change energy storage microcapsule; the third purpose of the present invention is to provide a thermochromic coating; the fourth purpose of the present invention is to provide a thermochromic phase-change energy storage microcapsule, or the application of a thermochromic coating.
[0006] The basic principle of the present invention is described as follows:
[0007] 1) The main feature of Pickering emulsion is that nanoparticles are used as emulsifiers to stabilize the emulsion system. The amount of emulsifier used is lower, the stability is better, the particle size of the dispersed phase in the emulsion is more uniform and controllable, and the foaming is lower. It is an ideal template for synthesizing microcapsules. However, to improve the encapsulation rate, it is necessary to provide an efficient Pickering stable particle. Cellulose nanocrystals (CNC) are usually extracted from cellulose materials by acid hydrolysis. As a natural derivative material, they are widely available and have the characteristics of high aspect ratio, high surface charge, easy surface modification, large specific surface area, high mechanical strength, high biocompatibility, good biodegradability, good wettability, and strong mechanical properties. Using cellulose nanocrystals as stabilizing particles can form a strongly entangled and disordered interface structure, which can effectively prevent the emulsion droplets from agglomerating, making the Pickering emulsion highly stable, green, environmentally friendly, and biodegradable.
[0008] 2) Compared with inorganic shells, polymers have excellent sealing properties and suitable plasticity. Therefore, the present invention selects resin prepolymers as wall materials including Pickering emulsions stabilized by cellulose nanocrystals, which not only enhances the mechanical properties of the material but also makes the shell thickness flexibly adjustable.
[0009] 3) The present invention first forms a CNC-stabilized Pickering emulsion, in which the CNC forms an inner coating layer of the core material, and then forms an outer coating layer by in-situ polymerization of a resin prepolymer. In this structure, the CNC will not fall off and can play a reinforcing role, thereby improving the mechanical properties of the material.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] The first aspect of the present invention provides a thermochromic phase-change energy storage microcapsule, comprising the following preparation materials: a core material, a Pickering emulsion template and a wall material;
[0012] The core material comprises the following components: a leucochromatin agent, a developer and a phase change material;
[0013] The Pickering emulsion template's stabilized particles include cellulose nanocrystals;
[0014] The wall material includes a resin prepolymer.
[0015] Preferably, the particle size of the thermochromic phase change energy storage microcapsule is 1 to 10 μm.
[0016] Preferably, the outer wall thickness of the thermochromic phase change energy storage microcapsule is 40 to 180 nm; further preferably, the outer wall thickness of the thermochromic phase change energy storage microcapsule is 55 to 160 nm.
[0017] Preferably, the core material content of the thermochromic phase change energy storage microcapsule is 80-95%; the core material content is calculated by dividing the enthalpy value per gram of the core material by the enthalpy value per gram of the thermochromic phase change energy storage microcapsule.
[0018] Preferably, the mass ratio of the leuco agent, the developer and the phase change material is 1:(1-5):(20-100); further preferably, the mass ratio of the leuco agent, the developer and the phase change material is 1:(2-4):(20-60).
[0019] Preferably, the leucochrome comprises at least one of crystal violet lactone, malachite green and thermosensitive green; further preferably, the leucochrome is crystal violet lactone.
[0020] Preferably, the developer includes at least one of dodecylphenol, bisphenol A, bisphenol F and bisphenol S.
[0021] Preferably, the phase change material includes at least one of saturated alkanes, esters, and organic oil mixtures.
[0022] Preferably, the saturated alkane includes at least one of n-octadecane and docosane.
[0023] Preferably, the esters include at least one of methyl octadecanoate, methyl behenate, and ethyl behenate.
[0024] Preferably, the organic oil mixture comprises at least one of coconut oil and palm oil.
[0025] Preferably, the resin prepolymer includes at least one of melamine resin prepolymer, urea-formaldehyde resin prepolymer and phenol-formaldehyde resin prepolymer; further preferably, the resin prepolymer is melamine resin prepolymer.
[0026] Preferably, the melamine resin prepolymer comprises the following preparation raw materials: melamine, formaldehyde and water.
[0027] Preferably, the mass ratio of melamine, formaldehyde and water is 1:(1.5-2.5):(5-8); further preferably, the mass ratio of melamine, formaldehyde and water is 1:(1.5-2):(5.5-7).
[0028] Preferably, the mass concentration of the formaldehyde is 35-38%.
[0029] Preferably, the melamine resin prepolymer is prepared by a method comprising the following steps:
[0030] Melamine and formaldehyde are mixed, water is added to adjust the pH value to 8-9, and the mixture is stirred and reacted at 65-75° C. for 15-25 minutes to obtain the melamine resin prepolymer.
[0031] Preferably, the thermochromic phase-change energy storage microcapsules include the following preparation raw materials: a leucochromic agent, a developer, a phase-change material, a resin prepolymer, cellulose nanocrystals, an alkali metal salt and water.
[0032] Preferably, the alkali metal salt includes at least one of potassium salt and sodium salt; further preferably, the alkali metal salt includes at least one of potassium chloride, potassium acetate, potassium citrate, sodium chloride, sodium acetate and sodium citrate.
[0033] Preferably, the thermochromic phase-change energy storage microcapsules provided by the present invention are reversible thermochromic phase-change energy storage microcapsules, and the color change temperature range of the thermochromic phase-change energy storage microcapsules is -30°C to 80°C.
[0034] The second aspect of the present invention provides a method for preparing the thermochromic phase-change energy storage microcapsule according to the first aspect of the present invention, comprising the following steps:
[0035] S1, melting and mixing the leuco agent, the developer and the phase change material to obtain an oil phase;
[0036] S2, mixing cellulose nanocrystals, alkali metal salt and water to obtain an aqueous phase;
[0037] S3, mixing the oil phase with the water phase, emulsifying, and obtaining a Pickering emulsion stabilized by cellulose nanocrystals;
[0038] S4, adding the resin prepolymer dropwise to the Pickering emulsion stabilized by the cellulose nanocrystals to carry out an in-situ polymerization reaction to obtain the thermochromic phase change energy storage microcapsules.
[0039] Preferably, in the step S1, the temperature of the melt mixing is 100-130°C; more preferably, the temperature of the melt mixing is 100-120°C.
[0040] Preferably, in step S1, the melt mixing time is 1 to 3 hours; more preferably, the melt mixing time is 1 to 2 hours.
[0041] Preferably, in step S2, the mass ratio of the cellulose nanocrystals, the alkali metal salt and water is 1:(0.8-1.2):(93-198); further preferably, the mass ratio of the cellulose nanocrystals, the alkali metal salt and water is 1:1:(140-198).
[0042] Preferably, in step S2, the cellulose nanocrystals are first mixed with water and ultrasonically dispersed for 5 to 20 minutes, and then an alkali metal salt is added and shaken to dissolve to obtain a cellulose nanocrystal dispersion as an aqueous phase.
[0043] Specifically, the addition of alkali metal salts can play a role in shielding ionic strength.
[0044] Preferably, in step S3, the mass ratio of the oil phase to the water phase is 1:(1-5).
[0045] Preferably, in step S3, the emulsification time is 10 to 20 minutes; more preferably, the emulsification time is 10 to 15 minutes.
[0046] Preferably, in step S3, the emulsification process is assisted by ultrasound.
[0047] Preferably, in step S4, the mass ratio of the resin prepolymer to the Pickering emulsion stabilized by cellulose nanocrystals is 1:(2-3).
[0048] Preferably, in step S4, the resin prepolymer is added at a speed of 5 to 15 μL / s; more preferably, the resin prepolymer is added at a speed of 8 to 12 μL / s. The resin prepolymer should be added to the Pickering emulsion stabilized by the cellulose nanocrystals at a slow and steady speed to avoid excessive local concentration due to excessively fast drop acceleration, resulting in poor shell coating effect.
[0049] Preferably, in the step S4, the polymerization reaction temperature is 60-80°C; more preferably, the polymerization reaction temperature is 65-75°C.
[0050] Preferably, in step S4, the polymerization reaction time is 2 to 4 hours; further preferably, the polymerization reaction time is 2 to 3 hours.
[0051] Preferably, the step S4 further comprises adjusting the pH value of the reaction system to 3-4.
[0052] Preferably, in the step S4, the process of adding the resin prepolymer dropwise is supplemented with stirring, and the stirring speed is 200-300 rpm.
[0053] Preferably, in the step S4, after the polymerization reaction is completed, the steps of suction filtration, washing and freeze drying are further included; and the freeze drying time is 20 to 25 hours.
[0054] The third aspect of the present invention provides a thermochromic coating, comprising the thermochromic phase-change energy storage microcapsules described in the first aspect of the present invention; the mass percentage of the thermochromic phase-change energy storage microcapsules is 15-25%.
[0055] Preferably, the thermochromic coating further comprises waterborne polyurethane.
[0056] Preferably, the mass ratio of the thermochromic phase change energy storage microcapsules to the aqueous polyurethane is 1:(3-6).
[0057] The fourth aspect of the present invention provides the application of the thermochromic phase-change energy storage microcapsule described in the first aspect of the present invention, or the thermochromic coating described in the third aspect in the field of art.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] 1) The thermochromic phase change energy storage microcapsules provided by the present invention use cellulose nanocrystals as Pickering emulsion stabilizing particles, the raw materials are easily available, the thermochromic phase change energy storage microcapsules have good stability, good coating effect, are environmentally friendly and pollution-free, have sensitive temperature response, reversible color change, a wide color change and energy storage temperature range, good thermal stability of the material, and good energy storage performance.
[0060] 2) The preparation method of the thermochromic phase-change energy storage microcapsules provided by the present invention has simple steps, is easy to operate, and is easy to realize large-scale production. The thickness of the microcapsule shell can be changed by changing the amount of resin prepolymer added.
[0061] 3) The thermochromic coating provided by the present invention contains thermochromic phase-change energy storage microcapsules, which can be used for coating or painting on the surface of products. It has bright colors and sensitive temperature response, which can increase the ornamental value of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 Schematic diagram of the preparation method of the thermochromic phase-change energy storage microcapsules in the embodiment;
[0063] Figure 2 This is a SEM image of the thermochromic phase-change energy storage microcapsule in Example 1 magnified 5000 times;
[0064] Figure 3 This is a SEM image of the thermochromic phase-change energy storage microcapsule in Example 1 magnified 10,000 times;
[0065] Figure 4The cross-sectional view (a) of the thermochromic phase-change energy storage microcapsule in Example 1 magnified 2500 times, the cross-sectional view (b) of the thermochromic phase-change energy storage microcapsule in Example 1 magnified 10000 times, the cross-sectional view (c) of the thermochromic phase-change energy storage microcapsule in Example 4 magnified 2500 times, and the cross-sectional view (d) of the thermochromic phase-change energy storage microcapsule in Example 4 magnified 10000 times;
[0066] Figure 5 This is a color change diagram of the thermochromic phase-change energy storage microcapsule in Example 1 at 20-80°C;
[0067] Figure 6 This is the color change diagram of the thermochromic phase-change energy storage microcapsule in Example 1 at -30 to 20°C;
[0068] Figure 7 The DSC cycle curve diagram of the thermochromic phase-change energy storage microcapsule in Example 1;
[0069] Figure 8 This is a coating application effect diagram of the coating in Application Example 1;
[0070] Fig. 9 This is a picture showing the painting application effect of the coating in Application Example 2. DETAILED DESCRIPTION
[0071] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0072] Figure 1 The schematic diagram of the preparation method of the thermochromic phase-change energy storage microcapsules in the embodiment is as follows. Figure 1 The preparation of thermochromic phase-changing energy storage microcapsules is described:
[0073] Example 1
[0074] This embodiment provides a thermochromic phase-change energy storage microcapsule, which is prepared by the following steps:
[0075] S1. Mix 0.22 g of crystal violet lactone, 0.66 g of bisphenol A and 11.11 g of methyl docosanoate and heat to 120° C., and stir for 1 h until the three are completely mixed into a transparent liquid to form an oil phase;
[0076] S2, weigh 0.09 g of CNC and add it to 17.82 g of water, use a cell disruptor to sonicate for 15 min, then add 0.09 g of sodium chloride, shake it to fully dissolve it to obtain a CNC dispersion to form an aqueous phase;
[0077] S3, adding the oil phase obtained in step S1 to the CNC dispersion obtained in step S2, and performing ultrasonic emulsification for 15 minutes using a cell disruptor to form a CNC-stabilized Pickering emulsion;
[0078] S4, weighing 1.26g of melamine and 2.43g of 37wt% formaldehyde aqueous solution, adding 7mL of water and adjusting the pH to 8-9, stirring and reacting at 70°C for 20min to obtain a transparent melamine resin prepolymer, keeping the emulsion obtained in step S3 at 70°C, stirring at a rate of 250rpm, slowly adding the melamine resin prepolymer to the emulsion at a rate of 10uL / s using a pipette, and then adjusting the pH to 3-4 using 1mol / L HCl, and reacting for 3h;
[0079] S5. The product obtained in step S4 is filtered and washed, and freeze-dried for 24 hours to obtain thermochromic phase-change energy storage microcapsules.
[0080] Example 2
[0081] This embodiment provides a thermochromic phase-change energy storage microcapsule, which is prepared by the following steps:
[0082] S1. Mix 0.166 g of crystal violet lactone, 0.5 g of dodecylphenol and 8.33 g of n-octadecane, heat to 100° C., and stir for 2 h until the three are completely mixed into a transparent liquid to form an oil phase;
[0083] S2, weigh 0.105 g of CNC and add it to 20.79 g of water, use a cell disruptor to sonicate for 5 min, then add 0.105 g of sodium chloride, shake it to fully dissolve it, and obtain a CNC dispersion to form an aqueous phase;
[0084] S3, adding the oil phase obtained in step S1 to the CNC dispersion obtained in step S2, and performing ultrasonic emulsification for 15 minutes using a cell disruptor to form a CNC-stabilized Pickering emulsion;
[0085] S4, weigh 1.3g of melamine and 2.5g of 37wt% formaldehyde aqueous solution, add 9mL of water and adjust the pH to 8-9, stir and react at 70°C for 20min to obtain a transparent melamine resin prepolymer, keep the emulsion obtained in step S3 at 70°C, stir at 250rpm, slowly add the melamine resin prepolymer to the emulsion at a speed of 10uL / s using a pipette, adjust the pH to 3-4 using 1mol / L HCl, and react for 3h;
[0086] S5. The product obtained in step S4 is filtered and washed, and freeze-dried for 24 hours to obtain thermochromic phase-change energy storage microcapsules.
[0087] Example 3
[0088] This embodiment provides a thermochromic phase-change energy storage microcapsule, which is prepared by the following steps:
[0089] S1. Mix 0.166 g of crystal violet lactone, 0.5 g of bisphenol A, 4 g of n-octadecane, 4.33 g of docosanoic acid methyl ester, heat to 120° C., and stir for 2 h until the three are completely mixed into a transparent liquid to form an oil phase;
[0090] S2, weigh 0.105 g of CNC and add it to 20.79 g of water, use a cell disruptor to sonicate for 5 min, then add 0.105 g of sodium chloride, shake it to fully dissolve it, and obtain a CNC dispersion to form an aqueous phase;
[0091] S3, adding the oil phase obtained in step S1 to the CNC dispersion obtained in step S2, and performing ultrasonic emulsification for 15 minutes using a cell disruptor to form a CNC-stabilized Pickering emulsion;
[0092] S4, weigh 1.3g of melamine and 2.5g of 37wt% formaldehyde aqueous solution, add 9mL of water and adjust the pH to 8-9, stir and react at 70°C for 20min to obtain a transparent melamine resin prepolymer, keep the emulsion obtained in step S3 at 70°C, stir at 250rpm, slowly add the melamine resin prepolymer to the emulsion at a speed of 10uL / s using a pipette, adjust the pH to 3-4 using 1mol / L HCl, and react for 3h;
[0093] S5. The product obtained in step S4 is filtered and washed, and freeze-dried for 24 hours to obtain thermochromic phase-change energy storage microcapsules.
[0094] Example 4
[0095] This embodiment provides a thermochromic phase-change energy storage microcapsule, and the preparation method includes the following steps:
[0096] S1. Mix 0.22 g of crystal violet lactone, 0.66 g of bisphenol A and 11.11 g of methyl docosanoate and heat to 120° C., and stir for 1 h until the three are completely mixed into a transparent liquid to form an oil phase;
[0097] S2, weigh 0.09 g of CNC and add it to 17.82 g of water, use a cell disruptor to sonicate for 15 min, then add 0.09 g of sodium chloride, shake it to fully dissolve it to obtain a CNC dispersion to form an aqueous phase;
[0098] S3, adding the oil phase obtained in step S1 to the CNC dispersion obtained in step S2, and performing ultrasonic emulsification for 15 minutes using a cell disruptor to form a CNC-stabilized Pickering emulsion;
[0099] S4, weigh 3.78g of melamine and 7.29g of 37wt% formaldehyde aqueous solution, add 21mL of water and adjust the pH to 8-9, stir and react at 70°C for 20min to obtain a transparent melamine resin prepolymer, keep the emulsion obtained in step S3 at 70°C, stir at 250rpm, slowly add the melamine resin prepolymer to the emulsion at a speed of 10uL / s using a pipette, adjust the pH to 3-4 using 1mol / L HCl, and react for 3h;
[0100] S5. The product obtained in step S4 is filtered and washed, and freeze-dried for 24 hours to obtain thermochromic phase-change energy storage microcapsules.
[0101] Application Example 1
[0102] The thermochromic phase change energy storage microcapsules obtained in Example 1 were stirred and mixed evenly with waterborne polyurethane (mass ratio 1:4) to obtain a thermochromic coating, and the coating was applied to the surface of a white object, and then the temperature of the object was raised to 70°C, and then the color change of the object was observed during the process of the temperature naturally dropping to 25°C.
[0103] Application Example 2
[0104] The thermochromic phase change energy storage microcapsules obtained in Example 1 were stirred and mixed evenly with waterborne polyurethane (mass ratio 1:4) to obtain a thermochromic coating, which was used for painting. The temperature of the painting was then raised to 70°C, and then the color change of the painting was observed during the process of the temperature naturally dropping to 25°C.
[0105] Performance Testing
[0106] 1. Observe the morphology of the thermochromic phase-change energy storage microcapsules in Example 1 using a scanning electron microscope:
[0107] Figure 2 This is a SEM image of the thermochromic phase-change energy storage microcapsule in Example 1 magnified 5000 times. Figure 2 It can be seen that the thermochromic phase change energy storage microcapsules in Example 1 have complete morphology and regular shape, the capsule particle size is about 1 to 10 μm, the particle size is relatively uniform, and the capsule material coating is good.
[0108] Figure 3 The SEM image of the thermochromic phase-change energy storage microcapsule in Example 1 is magnified 10,000 times. Figure 3 It can be seen that the microcapsules are regular spherical and the phase change material is well coated without leakage.
[0109] Figure 4The cross-sectional view (a) of the thermochromic phase-change energy storage microcapsule in Example 1 magnified 2500 times, the cross-sectional view (b) of the thermochromic phase-change energy storage microcapsule in Example 1 magnified 10000 times, the cross-sectional view (c) of the thermochromic phase-change energy storage microcapsule in Example 4 magnified 2500 times, and the cross-sectional view (d) of the thermochromic phase-change energy storage microcapsule in Example 4 magnified 10000 times. The difference between Example 1 and Example 4 is only that the amount of the resin prepolymer is different. Figure 4 It can be seen that when the amount of the resin prepolymer in Example 4 is changed to three times that in Example 1, the shell thickness of the microcapsule material increases from 55nm ( Figure 4 (b)) increases to 160nm( Figure 4 (d)), therefore, when only the amount of the resin prepolymer is changed during the preparation process, the shell thickness of the microcapsule can be flexibly adjusted.
[0110] By using the formula for calculating the coverage rate: coverage rate = phase change enthalpy of microcapsule material / phase change enthalpy of microcapsule core material*100%, it is calculated that the coverage rates of the thermochromic phase change energy storage microcapsules in Examples 1-4 are 91.81%, 93.42%, 90.84% and 95.63%, respectively. It can be seen that the coverage rate of the capsule material is relatively high, which is consistent with the results of scanning electron microscopy observations.
[0111] 2. The color change effect of the thermochromic phase change energy storage microcapsules in Example 1 was tested, and the temperature change ranges were 20 to 80°C and -30 to 20°C respectively:
[0112] Figure 5 is the color change diagram of the thermochromic phase-change energy storage microcapsule in Example 1 at 20-80°C. Figure 5 It can be seen that in the range of 20 to 80°C, as the temperature increases, the color of the thermochromic phase change energy storage microcapsules gradually changes from blue to white. When the temperature gradually drops from 80°C to 20°C, the color of the thermochromic phase change energy storage microcapsules gradually returns from white to blue.
[0113] Figure 6 The color change diagram of the thermochromic phase-change energy storage microcapsule in Example 1 at -30 to 20°C is shown in FIG. Figure 6 It can be seen that the microcapsule material appears blue under low temperature (-30°C) conditions, and the blue color gradually becomes lighter as the temperature gradually increases.
[0114] It can be seen that the thermochromic phase change energy storage microcapsules in Example 1 are thermochromic phase change energy storage microcapsules. The material has sensitive temperature response, reversible color change with temperature, and a wide color change temperature range.
[0115] 3. The phase change enthalpy performance of the thermochromic phase change energy storage microcapsules in Example 1 was tested using differential scanning calorimetry (DSC) Q2000 from TA Corporation of the United States:
[0116] Figure 7 is the DSC cycle curve of the thermochromic phase-change energy storage microcapsule in Example 1. The following Table 1 shows the phase change enthalpy and enthalpy retention rate obtained according to the DSC cycle curve. Figure 7 As shown in Table 1, after 100 cycles of scanning, the retention rate of the microcapsule enthalpy value reached more than 99%, indicating that it has extremely high thermal stability.
[0117] Table 1 Phase change enthalpy and enthalpy retention rate of thermochromic phase change energy storage microcapsules
[0118]
[0119] Figure 8 This is a coating application effect diagram of the coating in Application Example 1, from left to right, the color change of the object during the natural cooling process from 70°C to 25°C; Fig. 9 The effect diagram of the paint application in Application Example 2 is shown in Figure 2. From left to right, the color changes of the object during the natural cooling process from 70°C to 25°C. Figure 8 and Fig. 9 It can be seen that after the thermochromic phase change energy storage microcapsules in Example 1 are mixed with water-based polyurethane to form a coating, the coating can be applied to the surface of an object or used for painting, which can increase the ornamental value of the product. During the natural cooling of the product temperature from 70°C to 25°C, the overall color gradually changes from white to blue. However, it can be observed that due to the uneven coating thickness and surface temperature, the color distribution of the object is also different. The high temperature part is still white, and the low temperature part is blue, which reflects that the coating containing the thermochromic phase change energy storage microcapsules also has extremely high temperature sensitivity.
[0120] The thermochromic phase-change energy storage microcapsules provided by the present invention have uniform particle size, good coating effect, and no leakage of phase-change material; the thermochromic phase-change energy storage microcapsules are reversible thermochromic thermochromic phase-change energy storage microcapsules, and have high sensitivity to color changes with temperature within -30 to 80°C, bright colors at low temperatures, high material enthalpy retention rate after multiple cycle scanning, and good thermal stability; the thermochromic paint containing the thermochromic phase-change energy storage microcapsules can be coated on the surface of products or directly used for painting, which can increase artistic appreciation, and the application effect of the thermochromic phase-change energy storage microcapsules and the thermochromic paint in the field of art is good.
Claims
1. A thermochromic phase-change energy storage microcapsule, characterized in that: The preparation comprises the following raw materials: core material, Pickering emulsion template and wall material; The core material comprises the following components: a leucochromatin agent, a developer and a phase change material; The Pickering emulsion template's stabilized particles include cellulose nanocrystals; The wall material includes a resin prepolymer.
2. The thermochromic phase-change energy storage microcapsule according to claim 1, characterized in that: The particle size of the thermochromic phase-change energy storage microcapsule is 1 to 10 μm; And / or, the outer wall thickness of the thermochromic phase change energy storage microcapsule is 40 to 180 nm.
3. The thermochromic phase-change energy storage microcapsule according to claim 1, characterized in that: The mass ratio of the leuco agent, the developer and the phase change material is 1:(1-5):(20-100).
4. The thermochromic phase-change energy storage microcapsule according to claim 1, characterized in that: The leucochrome agent comprises at least one of crystal violet lactone, malachite green and thermosensitive green; And / or, the developer includes at least one of dodecylphenol, bisphenol A, bisphenol F, and bisphenol S; And / or, the phase change material includes at least one of saturated alkanes, esters, and organic oil mixtures; And / or, the resin prepolymer includes at least one of a melamine resin prepolymer, a urea-formaldehyde resin prepolymer, and a phenol-formaldehyde resin prepolymer.
5. The thermochromic phase-change energy storage microcapsule according to any one of claims 1 to 4, characterized in that: The thermochromic phase-change energy storage microcapsule comprises the following preparation raw materials: a leucochromic agent, a developer, a phase-change material, a resin prepolymer, cellulose nanocrystals, an alkali metal salt and water.
6. The method for preparing the thermochromic phase-change energy storage microcapsule according to claim 5, characterized in that: The following steps are involved: S1, melting and mixing the leuco agent, the developer and the phase change material to obtain an oil phase; S2, mixing cellulose nanocrystals, alkali metal salt and water to obtain an aqueous phase; S3, mixing the oil phase with the water phase, emulsifying, and obtaining a Pickering emulsion stabilized by cellulose nanocrystals; S4, adding the resin prepolymer dropwise to the Pickering emulsion stabilized by the cellulose nanocrystals to carry out an in-situ polymerization reaction to obtain the thermochromic phase change energy storage microcapsules.
7. The preparation method according to claim 6, characterized in that: In the step S2, the mass ratio of the cellulose nanocrystals, the alkali metal salt and water is 1:(0.8-1.2):(93-198); And / or, in step S3, the mass ratio of the oil phase to the water phase is 1:(1-5).
8. The preparation method according to claim 6, characterized in that: In the step S4, the mass ratio of the resin prepolymer to the Pickering emulsion stabilized by cellulose nanocrystals is 1:(2-3); And / or, the resin prepolymer has a dropping speed of 5 to 15 μL / s.
9. A thermochromic coating, characterized in that: The thermochromic phase-change energy storage microcapsule comprises the thermochromic phase-change energy storage microcapsule according to any one of claims 1 to 4; The mass percentage of the thermochromic phase-change energy storage microcapsules is 15-25%.
10. Use of the thermochromic phase-change energy storage microcapsule according to any one of claims 1 to 4, or the thermochromic coating according to claim 9 in the field of art.
Citation Information
Cited By
TiO2 (at) MUF hybrid shell thermochromic phase change microcapsule as well as preparation method and application thereof
CN121610255A
TiO2@MUF hybrid shell thermochromic phase change microcapsule and preparation method and application thereof
CN121610255B
Red light enhanced temperature-controllable non-woven fabric and preparation method thereof
CN122327555A
